THE INFLUENCE OF HUMAN CAPITAL, STRUCTURAL CAPITAL AND RELATIONAL CAPITAL TO THE PERFORMANCE OF COOPERATIONWITH COMPETITIVE ADVANTAGE AS INTERVENING VARIABLE OF COOPERATION IN SOUTH TANGERANG - Azzahra, Khoirunnisa (EAJ (Economic and Accounting Journal), 2018)
This Research is about to test the influence of human capital, structural capital and relational capital to the performance of the Koperasi with competitive advantage as intervening variable by testing the direct influence of human capital, structural capital and relational capital performance of the Koperasi and the indirect influence with competitive advantage as intervening variable. The instability of growth of the Koperasi in Indonesia is caused by the human resource quality which has not developed optimally. This caused had become the motivation of the research in doing this research.